Developmental regulation of Wnt signaling by Nagk and the UDP-GlcNAc salvage pathway. (April 2019) - Neitzel, Leif R.; Spencer, Zachary T.; Nayak, Anmada; Cselenyi, Christopher S.; Benchabane, Hassina; Youngblood, CheyAnne Q.; Zouaoui, Alya; Ng, Victoria; Stephens, Leah; Hann, Trevor; Patton, James G.; Robbins, David; et al.
Abstract: In a screen for human kinases that regulate Xenopus laevis embryogenesis, we identified Nagk and other components of the UDP-GlcNAc glycosylation salvage pathway as regulators of anteroposterior patterning and Wnt signaling. We find that the salvage pathway does not affect other major embryonic signaling pathways (Fgf, TGFβ, Notch, or Shh), thereby demonstrating specificity for Wnt signaling. We show that the role of the salvage pathway in Wnt signaling is evolutionarily conserved in zebrafish and Drosophila . Finally, we show that GlcNAc is essential for the growth of intestinal enteroids, which are highly dependent on Wnt signaling for growth and maintenance. We propose that the Wnt pathway is sensitive to alterations in the glycosylation state of a cell and acts as a nutritional sensor in order to couple growth/proliferation with its metabolic status. We also propose that the clinical manifestations observed in congenital disorders of glycosylation (CDG) in humans may be due, in part, to their effects on Wnt signaling during development. Highlights: The UDP-GlcNAc glycosylation salvage pathway regulates axiation in Xenopus embryos. Disruption of Xenopus axiation by the salvage pathway is mediated by Wnt signaling. The salvage pathway regulates Wnt but not Fgf, TGFβ, Notch, or Shh signaling. Regulation of Wnt signaling by the salvage pathway is evolutionarily conserved.